2013
DOI: 10.1007/s00374-013-0893-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of redox conditions and rice straw incorporation on nitrogen availability in fertilized paddy soils

Abstract: Temporal nitrogen (N) availability in fertilized rice paddies is the result of a balance of processes, mainly the gross rates of N mineralization, microbial and abiotic immobilization and N losses. Water and crop residue management practices often confound these established relationships making N the most difficult nutrient to manage in rice cropping systems. To investigate and quantify the interactive effects of soil redox conditions and straw incorporation on temporal fertilizer-N availability we treated a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…The negative effects of straw incorporation in the early stage have been explained by N starvation (Fig. 3), toxic substances and intensely reducing conditions caused by straw decomposition (Tanaka and Nishida, 1996;Cucu et al, 2014). The variety of effects of straw incorporation at maturity are probably due to the differences in soil N availability; N fertilizer level and application method; the amount and method of straw incorporated; or the length of the growing season.…”
Section: Effects Of Straw Incorporation On Rice Growth (Shoot Dm and mentioning
confidence: 99%
See 3 more Smart Citations
“…The negative effects of straw incorporation in the early stage have been explained by N starvation (Fig. 3), toxic substances and intensely reducing conditions caused by straw decomposition (Tanaka and Nishida, 1996;Cucu et al, 2014). The variety of effects of straw incorporation at maturity are probably due to the differences in soil N availability; N fertilizer level and application method; the amount and method of straw incorporated; or the length of the growing season.…”
Section: Effects Of Straw Incorporation On Rice Growth (Shoot Dm and mentioning
confidence: 99%
“…There are three possible reasons for this. (1) In the early stage of growth, intensely reducing conditions as a result of straw decomposition likely restricted the growth of subsurface roots; however, in the late stage (as the straw decomposition rate was falling), there were no longer significant differences in the redox conditions between the two straw treatments (Gao et al, 2004;Cucu et al, 2014). Olk et al (2007) reported that the decomposition of crop residues in a field trial was largely completed after 6 weeks of incorporation.…”
Section: Effects Of Straw Incorporation On Subsurface Roots (Dm and Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant stressors impact yields of both summer and winter crops, including canola, wheat, sugar cane, corn, cotton, and rice. The main abiotic plant stressors that impact crop growth include fluctuating temperatures, soil pH, salinity, soil water availability (drought), diurnal cycling changes, and availability of soil nutrients [1][2][3][4][5][6][7][8][9][10][11][12]. Summer crops grown in Australia, including rice, cotton, and sugar cane, require high volumes of water, which is applied using irrigation systems.…”
Section: Introductionmentioning
confidence: 99%